Pengaruh Self-Efficacy Dan Disiplin Kerja Terhadap Kinerja Aryawan Universitas XYZ Di Cikarang Bekasi - Ahmad Kultur Hia; Desi Ayu Tiana; Yanto Lesmana; Rustomo Rustomo (Journal on Education, 2024)
Higher education providers require the quality of their employees as servants to customers. The importance of self-efficacy of students, both lecturers and staff, to serve students as customers. This research is to find out how much contribution and influence self-efficacy and work discipline have on employee performance at XYZ University. The ability to control oneself as an employee with various limitations, and with the capital of discipline at work. This research uses a quantitative method with test equipment using a questionnaire with a Likert scale. The population and sample are all employees at XYZ University as a saturated sample. The data declared valid and reliable for the questionnaire distributed to respondents, with a strong positive contribution and significant influence and a very strong positive relationship. It hoped that XYZ University can improve the ability of its employees to be disciplined and self-controlled so that performance is achieved.